Disaster Ergonomics: Human Factors in COVID-19 Pandemic Emergency Management. (November 2020) - Sasangohar, Farzan; Moats, Jason; Mehta, Ranjana; Peres, S. Camille
Objective: We aimed to identify opportunities for application of human factors knowledge base to mitigate disaster management (DM) challenges associated with the unique characteristics of the COVID-19 pandemic. Background: The role of DM is to minimize and prevent further spread of the contagion over an extended period of time. This requires addressing large-scale logistics, coordination, and specialized training needs. However, DM-related challenges during the pandemic response and recovery are significantly different than with other kinds of disasters. Method: An expert review was conducted to document issues relevant to human factors and ergonomics (HFE) in DM. Results: The response to the COVID-19 crisis has presented complex and unique challenges to DM and public health practitioners. Compared to other disasters and previous pandemics, the COVID-19 outbreak has had an unprecedented scale, magnitude, and propagation rate. The high technical complexity of response and DM coupled with lack of mental model and expertise to respond to such a unique disaster has seriously challenged the response work systems. Recent research has investigated the role of HFE in modeling DM systems' characteristics to improve resilience, accelerating emergency management expertise, developing agile training methods to facilitate dynamically changing response, improving communication and coordination among system elements, mitigating occupational hazards including guidelines for the design of personal protective equipment, and improving procedures to enhance efficiency and effectiveness of response efforts. Conclusion: This short review highlights the potential for the field's contribution to proactive and resilient DM for the ongoing and future pandemics.